Pancreatic and Colonic Abscess Formation Secondary to HELLP Syndrome - James M. O'Brien; Nicole Pursell; Fred Fumia (Hindawi Limited, 2015)
Preeclampsia and the variant HELLP syndrome are systemic conditions associated with vascular changes resulting in vasoconstriction. Most commonly, patients present with elevated blood pressure and proteinuria, with a background of complaints such as headache, scotoma, and right upper quadrant pain. The systemic vascular changes experienced can target any organ system, oftentimes with more than one organ system being involved. We present the case of a patient admitted with HELLP syndrome who subsequently developed multisystem organ dysfunction, including placental abruption, disseminated intravascular coagulopathy, acute renal failure, colitis, abdominal ascites, pancreatitis, and the development of pancreatic and colonic abscesses.